Actualization of Numeracy Literacy in Character Education at Elementary School Level in the Era of Disruption - Tanjung, Bahdin Nur (Lembaga Riset Mutiara Akbar, 2024)
This research aims first to determine the extent of the role of literacy and numeracy in the educational context in building character. Furthermore, to find out what obstacles make literacy and numeracy does not work well well in the educational environment in forming character. The research method used in this article is a systematic literature review, the author searches for published articles related to the title or research topic that the researcher has determined, the articles searched are limited to 50 articles, then the researcher filters them to 20 articles that are considered appropriate and close to each other. to answer this research. The results of the research show that as many as 20 articles from the search results show that the role of literacy and numeracy has a significant impact on improving numeracy and reading skills at primary school level, especially from the results of PISA and OECD data which reveal that Indonesia is still experiencing a decline in terms of literacy and numeracy. From the search results, it can be concluded that literacy and numeracy have a role in character formation in the world of education. So, researchers provide recommendations for the need for support from the government, educational institutions, students' environment and parents to work together to improve students' abilities in calculating and reading while aiming to shape the character of each student.